A/the common good - Burbidge, D (Oxford University Press, 2024)
The emerging school of “common good constitutionalism” takes a classical natural law approach of identifying the central case of law and constitutionalism, recognising that a state may make positive law in part based on circumstance, convenience, or a need for social coordination. While law under the classical approach is rooted in realising the common good of the complete community, this ideal does not dictate all of law’s specifics. Nevertheless, there is a difficulty within the emerging school of common good constitutionalism in the way it seeks to respect the diversity of constitutional orders while retaining a single reference point of the common good. Adrian Vermeule and others appeal to positive law as the determinatio through which public authorities make concrete the state’s pursuit of the common good. But there is often a gulf between common good principles and the determinatio of law. The move from principles to the legitimacy or justness of positive law lies, for Vermeule, in joining-up the central case method of natural law with a singular notion of the common good. The article criticises this reliance, arguing that the central case method cannot be used to determine law in the sense of the determinatio of positive law. In his articulation of central case methodology, John Finnis is, by contrast, careful to leave space for varieties of coordination and forms of justice, such that the central case method plays a limited role in establishing what counts as common goods. Rather, the central case method identifies what law is. The same delicacy is present in Aquinas, who does not in fact define law as an ordinance of reason for the common good in the way that common good constitutionalists so far would like it to mean, because there are no articles in Latin grammar. In this regard, common good constitutionalism’s mistake is unfortunately in keeping with the majority of jurisprudence, which commits the logical fallacy that an internally consistent account of law is externally authoritative—in other words, that harmony in the way in which laws and legal principles relate to themselves can act as a basis to the body politic’s prioritisation of some goods over others.